Enhancing SS 400 Metal Weld Quality through Current Optimization: Meningkatkan Kualitas Pengelasan Logam SS 400 melalui Optimalisasi Arus - Sudrajat , Risvanda Amin; Akbar , Ali (Universitas Muhammadiyah Sidoarjo, 2024)
This study investigates the impact of varying welding electric current strengths (70 A, 100 A, and 130 A) on SS 400 metal welding using Shielded Metal Arc Welding (SMAW) with an E6013 electrode. The aim is to identify the optimal current strength for minimizing defects and enhancing weld quality. Liquid penetrant testing is employed to detect welding defects, with results showing that excessively low or high current strengths result in increased defects, such as holes and red spots. The findings highlight the importance of utilizing an electric current around 100 A to achieve optimal weld quality, while liquid penetrant testing proves effective for defect detection and quality assessment, aiding in early prevention of corrosion and other issues in welding processes. Highlight: Optimizing Welding Parameters: Essential for minimizing defects and enhancing SS 400 metal weld quality. Effective Defect Detection: Liquid penetrant testing aids in identifying welding flaws efficiently. Enhanced Weld Quality: Utilizing optimal electric current strength improves weld integrity effectively. Keywoard: Welding, SS 400 metal, Shielded Metal Arc Welding, Electric current, Liquid penetrant testing